Sorption of thorium using magnetic graphene oxide polypyrrole composite synthesized from natural source - Gado, M. A. (Separation science and technology, 2018)
Polypyrrole magnetic graphene oxide (PPy/MGO) composites has been synthesized from natural source (water hyacinth roots) using polymerization technique for Th(IV) ions pre-concentration from aqueous solutions. The effects of controlling factor have been studied using batch technique. The obtained results show that the maximum Th(IV) adsorption capacity by PPy/MGO composite is 277.8 mg/g at pH 4, which is higher than traditional adsorbents. PPy/MGO composite also presents excellent regeneration/reuse property. Due to the high adsorption capacity of Th(IV), PPy/MGO composite can be used in nuclear fuel achievement and for Th(IV) environmental pollution cleanup.